2022
DOI: 10.1002/mrm.29456
|View full text |Cite
|
Sign up to set email alerts
|

The future is 2D: spectral‐temporal fitting of dynamic MRS data provides exponential gains in precision over conventional approaches

Abstract: Purpose Many MRS paradigms produce 2D spectral‐temporal datasets, including diffusion‐weighted, functional, and hyperpolarized and enriched (carbon‐13, deuterium) experiments. Conventionally, temporal parameters—such as T2, T1, or diffusion constants—are assessed by first fitting each spectrum independently and subsequently fitting a temporal model (1D fitting). We investigated whether simultaneously fitting the entire dataset using a single spectral‐temporal model (2D fitting) would improve the precision of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 57 publications
0
33
0
Order By: Relevance
“…Indeed, a recent study on a set of synthetic dMRS spectra found a more reliable estimate of diffusion and tissue properties when simultaneous fitting is applied. 92 This is supported by Tal et al, 93 showing that simultaneous 2D fitting improved precision by at least 20% compared to 1D fitting.…”
Section: Simultaneous (2d) Fittingmentioning
confidence: 77%
“…Indeed, a recent study on a set of synthetic dMRS spectra found a more reliable estimate of diffusion and tissue properties when simultaneous fitting is applied. 92 This is supported by Tal et al, 93 showing that simultaneous 2D fitting improved precision by at least 20% compared to 1D fitting.…”
Section: Simultaneous (2d) Fittingmentioning
confidence: 77%
“…Recently the advantages of dynamic fitting of 2D data (also called spectral-temporal fitting) were demonstrated theoretically and numerically. 34 Here, we replicated these results using the software framework of FSL-MRS and extended the simulations from toy (two resonance) examples to realistic 1 H-fMRS data, containing many overlapping spectral resonances. Functional MRS temporally resolves MRS to detect changes in neurochemical concentrations (or metabolite visibility), induced by external sensory stimulus or otherwise evoked neural activity.…”
Section: Cs1 Functional Mrs: Replication and Extension Of Talmentioning
confidence: 66%
“…While the present analysis makes no particular assumptions regarding the shape of the GRF (beyond the restricted T S‐A range), we note that recent studies have begun to investigate putative metabolite response functions 99 ; once an appropriate response function is determined, incorporation of this into the present model (in place of the coarse binning) will be trivially accomplished, and may well improve sensitivity to subtle variations. Furthermore, while the present model reconstructs discrete sub‐spectra which are fitted independently using existing 1D modelling tools, we note recent developments towards simultaneous, 2D spectral‐temporal fitting 100 of multiple spectra linked by an arbitrary model, such as that implemented in the FSL‐MRS dynamic fitting module 22,101 . With appropriate constraints, incorporating our linear model into such an approach may further improve fitting performance, particularly for lower‐SNR cases.…”
Section: Discussionmentioning
confidence: 99%
“…Functional events were binned according to the achieved interval between stimulus and acquisition (T S-A ). Five bins (bin 1-5 ) were defined, with edges at [100,183,267,350] ms, open at either end, lower limits inclusive; the inner three bins evenly cover the nominated 100-350 ms T S-A range. This resulted in approximately 48 task-ON metabolite transients per bin (with some individual variation), and 320 task-OFF metabolite transients.…”
Section: Metabolite Sub-spectra: a Linear Model For Spectral Combinationmentioning
confidence: 99%